Pendampingan Wawasan Manajerial pada UMKM Burger Kessap di Malang sebagai Upaya Peningkatan Kualitas Usaha - Fahrizal; Ellena Yusvia Wardhani; Agung Winarno; Agus Hermawan (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Culinary Micro, Small, and Medium Enterprises (MSMEs) often face managerial and digitalization challenges. This community service activity aims to provide managerial insight assistance to the Burger Kessap MSME in Malang City to improve the quality and scale of its business. The method used is a needs-based approach consisting of four stages: needs analysis, priority setting, intervention planning, and implementation and evaluation. The results of the assistance indicate developments in key managerial aspects: (1) Finance, through the transition from manual recording to the use of daily cash books; (2) Marketing, by expanding reach through digital platforms (GoFood, GrabFood, ShopeeFood); and (3) Legality, with the issuance of a Business Identification Number (NIB). The conclusion of this activity is that interventions tailored to the specific needs of partners have proven effective in accelerating the transformation of MSMEs towards more professional and adaptive management in the digital era and can reach a wider consumer scale. Future recommendations are the importance of consistently maintaining the sustainability of these managerial practices and regular evaluation.